A Formal Approach to the Study of the Evolution and Commonality of Patterns. (February 2013) - Lee, Ji-Hyun; Park, Hyoung-June; Lim, Sungwoo; Kim, Sun-Joong
The formal approach outlined in this paper uses symbolic memes as a framework for the hierarchical deconstruction of a cultural artefact, the traditional Korean pattern known as bosangwhamun, to describe the evolutionary development of such a pattern using shape grammar rules. The formal descriptions of this pattern are thus the basis for generating its variations, and the process is used to evaluate the validity of the rules and their appropriateness for the study of bosangwhamun .